Postoperative opioid-free analgesia in elective bowel resection: Changes over time. Issue 7 (July 2021) - Patel, Ankoor; Rojas, Aram; Samson, David; Fakas, Steliana; Gachabayov, Mahir; L. Xu, Jeff; Latifi, Rifat; Bergamaschi, Roberto
In the pain management evolution, opioid-free analgesia and multimodal analgesia strategies have emerged as feasible in many surgical settings including colorectal surgery. This was a retrospective cohort study including patients having undergone elective bowel resection between February 2012 and June 2018 aiming to evaluate whether there was reduction in opioid use after implementation of opioid-free analgesia in one medical centre. Trend analysis was conducted using Joinpoint regression employing nine-month intervals. The primary outcome for each interval was the proportion of patients receiving postoperative opioid-free analgesia, defined as forgoing all opioid analgesics after the day of surgery. This study showed a significant increasing trend in opioid-free analgesia in elective bowel resection from 0 to 42.5% over 4.5 years.